Potential influence of courtyard on indoor environment conditions of office buildings - Hussien Abass Younis, Fatma (2016)
It is recognized that the air conditioning system is a major factor that influencing energy consumption in Malaysia. In fact, residential and non-residential buildings, become a subject to significant cooling necessities due to the high intensity of heat passing from building external envelope, the rely on mechanical cooling systems to provide best indoor condition was directed to increase the energy consumption. Due to this fact, many designers highlighted the potential influence of courtyards as a natural cooling technique to enhance indoor comfort for building users and consequently minimize space-cooling conditioning. This research investigates the courtyard attributes as a natural cooling technique in tropical climates, to provide indoor thermal condition at single, double and three-story buildings; furthermore, to achieve low energy office buildings in Kuala Lumpur and Johor. The research objectives are to investigate the history of the courtyard in Malaysia, to evaluate indoor environmental conditions at office buildings and finally to assess, the effectiveness of a courtyard on conserving energy in office buildings in Malaysia. The research method is a combination of literature review, environmental measurement, post occupancy evaluation and energy consumption data. To achieve the first objective of this research previous study assessed to gain information of the courtyard at vernacular architecture, contemporary vernacular and modern architecture in Malaysia, it started before independence in 1957 and transformed through time until the dawn of the new millennium. Furthermore, several environmental aspects such as air temperatures, relative humidity, and air velocity were measured using a portable instrument (Lutron LM 8000) and thermal comfort station (BABUC A). Whereas, the post-occupancy evaluation used to assess the level of indoor thermal condition at office buildings, at least, the energy data examined through the electricity bills for the at least one-year period. According to the last findings of this research, the influence of the courtyard on providing indoor thermal conditions achieved at single and three storey buildings, while for double storey building the indoor condition did not comply with ASHRAE- 55 and ISO 7730 standards. For the term low energy office buildings, the results illustrated that single and double storey office buildings considered as low energy office buildings, while for three storey office buildings the amount of energy that used did not comply with MS 1525 standard.